Electrochemical sensing of etoposide using carbon quantum dot modified glassy carbon electrode. Issue 9 (17th February 2016) - Nguyen, Hoai Viet; Richtera, Lukas; Moulick, Amitava; Xhaxhiu, Kledi; Kudr, Jiri; Cernei, Natalia; Polanska, Hana; Heger, Zbynek; Masarik, Michal; Kopel, Pavel; Stiborova, Marie; Eckschlager, Tomas; et al.
Abstract : In this study, carbon quantum dots were used for enhancement of the electrochemical signals of etoposide. Abstract : In this study, enhancement of the electrochemical signals of etoposide (ETO) measured by differential pulse voltammetry (DPV) by modifying a glassy carbon electrode (GCE) with carbon quantum dots (CQDs) is demonstrated. In comparison with a bare GCE, the modified GCE exhibited a higher sensitivity towards electrochemical detection of ETO. The lowest limit of detection was observed to be 5 nM ETO. Furthermore, scanning electron microscopy (SEM), fluorescence microscopy (FM), and electrochemical impedance spectroscopy (EIS) were employed for the further study of the working electrode surface after the modification with CQDs. Finally, the GCE modified with CQDs under optimized conditions was used to analyse real samples of ETO in the prostate cancer cell line PC3. After different incubation times (1, 3, 6, 9, 12, 18 and 24 h), these samples were then prepared prior to electrochemical detection by the GCE modified with CQDs. High performance liquid chromatography with an electrochemical detection method was employed to verify the results from the GCE modified with CQDs.